2019
DOI: 10.1103/physreva.99.053614
|View full text |Cite
|
Sign up to set email alerts
|

Quantum phases and topological properties of interacting fermions in one-dimensional superlattices

Abstract: The realization of artificial gauge fields in ultracold atomic gases has opened up a path towards experimental studies of topological insulators and, as an ultimate goal, topological quantum matter in many-body systems. As an alternative to the direct implementation of two-dimensional lattice Hamiltonians that host the quantum Hall effect and its variants, topological charge-pumping experiments provide an additional avenue towards studying many-body systems. Here, we consider an interacting two-component gas o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 99 publications
(181 reference statements)
1
29
0
Order By: Relevance
“…Here λ is the amplitude of the modulation, p is the size of the unit cell, and φ is the phase factor. These kinds of modulations are very common in researching topological insulators in 1D optical superlattices [17,23,27,39,40].…”
Section: Model and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Here λ is the amplitude of the modulation, p is the size of the unit cell, and φ is the phase factor. These kinds of modulations are very common in researching topological insulators in 1D optical superlattices [17,23,27,39,40].…”
Section: Model and Methodologymentioning
confidence: 99%
“…The 1D quasi-periodic superlattice has been attracting continuous investigations in the last decade, partially because of its nontrivial topological nature [17][18][19][20][21][22][23]. In a noninteracting setting, the essential physics behind it is well understood, that these 1D quasi-periodic models can be mapped to the 2D Harper-Hofstadter model [24,25] which is used to describe the quantum Hall effect [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…* heidrich-meisner@uni-goettingen. de In a previous work [20], we showed that Hubbard interactions in a fermionic, one-dimensional charge pump can change its topological properties: Without interactions, the Chern number is C = 2, but strong repulsion changes it to C = −1. Note that we change the sign convention for C relative to [20].…”
Section: Introductionmentioning
confidence: 95%
“…Besides, the interacting fermionic SSH model was shown to exhibit unusual correlation dynamics upon a quench [19], which can be attributed to a rich interplay between the presence of topological edge modes and spin-charge separation in one dimension. Finally, quantized pumps of interacting bosons [20] and fermions [21] were also recently investigated.…”
Section: Introductionmentioning
confidence: 99%